Kesehatan Jiwa Islam Telaah terhadap Pemikiran Abu Zaid al-Balkhi dalam Buku Maṣāliḥu al-Abdān wa al-Anfus - Isnaini Mar'ah Azizah; Aris Fauzan (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2021)
The discourse on mental health is often an interesting and beneficial discussion across time. There are many developing concepts adopted from western thoughts. The concept offered by Islamic Psychology has not been explored yet. One of them is the concept of mental health from the perspective of Abu Zaid al-Balkhi. This study aims to analyze the concept of Islamic mental health, specifically the thought of Abu Zaid al-Balkhi in the book Maṣāliḥu al-Abdān wa al-Anfus. By using a type of qualitative research with a descriptive-analytical method specifically in describing and analyzing mental health concepts, according to Abu Zaid al-Balkhi. Based on this research, it can be seen that mental health or a healthy soul is the stability of the soul’s strength in humans so that it can defeat the turmoil of psychiatric signs. Al-Balkhi classifies psychiatric symptoms into four groups, namely, sadness and anxiety (al-ḥuzn wal jazʻ), obsession (al-waswas), anger (al-gaḍab), and finally, fear and phobia (al-khauf wa al-fazʻ). To achieve happiness, humans should always try and strive for a balance between the body and soul. The attachment of both (body and soul) is in harmony with human construction, namely physical and spiritual. Caring for and maintaining health as a preventive effort is preferred than treating it if already sick. This is what distinguishes the concept of healing the soul of Islam, according to al-Balkhi, with the concept of western secular psychotherapy